Heart‐beat‐phase‐coherent Doppler optical coherence tomography for measuring pulsatile ocular blood flow. Issue 3 (5th June 2012) - Schmoll, Tilman; Leitgeb, Rainer A.
Abstract We introduce a Doppler OCT (DOCT) platform that is fully synchronized with the heart‐beat via a pulse oximeter. The system allows reconstructing heart‐beat‐phase‐coherent quantitative DOCT volumes. The method is to acquire a series of DOCT volumes and to record the pulse in parallel. The heartbeat data is used for triggering the start of each DOCT volume acquisition. The recorded volume series is registered to the level of capillaries using a cross‐volume registration. The information of the pulse phase is used to rearrange the tomograms in time, to obtain a series of phase coherent DOCT volumes over a pulse. We present Doppler angle independent quantitative evaluation of the absolute pulsatile blood flow within individual retinal vessels as well as of the total retinal blood flow over a full heartbeat cycle. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)